2016
DOI: 10.1038/cti.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Non‐small cell lung cancer is characterised by a distinct inflammatory signature in serum compared with chronic obstructive pulmonary disease

Abstract: Development of lung cancer is closely related to smoking in a majority of patients. Most smokers, however, do not develop lung cancer in spite of a high mutational load accumulating in the lung tissue. Here we investigate whether a cancer-specific footprint can be revealed by investigating circulating inflammatory markers in patients with non-small cell lung cancer (NSCLC) compared with patients with chronic obstructive pulmonary disease (COPD), both cohorts characterised by similar smoking history. Serum conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…Matsumoto et al, showed that higher levels of PDGF-bb were associated with poor prognosis in esophageal cancers, 31 while Eide et al found higher PDGF-bb serum levels in lung cancer compared to COPD patients. 32 In the MicMa cohort higher levels of PDGF were associated with worse prognosis, the same tendency although not significant, was observed in the DCTB cohort. The PDGF family of growth factors play a role in lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…Matsumoto et al, showed that higher levels of PDGF-bb were associated with poor prognosis in esophageal cancers, 31 while Eide et al found higher PDGF-bb serum levels in lung cancer compared to COPD patients. 32 In the MicMa cohort higher levels of PDGF were associated with worse prognosis, the same tendency although not significant, was observed in the DCTB cohort. The PDGF family of growth factors play a role in lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…It has been deeply investigated how various elements of the pathogenesis of COPD contributed to pathogenesis of lung cancer. Recently, the shift from Th1 to Th2 polarization of the immune response [40], the accumulation of IL-17 producing Th17 lymphocytes [41], the simultaneous overproduction of certain cytokines, chemokines and matrix metalloproteinases [42] have been raised as possible elements of carcinogenesis in those who smoke and have suffered from COPD previously. *Cox-regression model also included the type of chemotherapy, which did not influence PFS (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials evaluating immune checkpoint inhibitors (ICI), such as antibodies to anti-programmed cell death protein 1 (PD-1) and its ligand (PD-L1), have demonstrated that blocking such inhibitory receptors and ligands provides benefit to patients with cancers such as non-small cell lung cancer (NSCLC), urothelial cancer, renal cell carcinoma, melanoma, and ovarian cancer (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Furthermore, patients in whom the immune checkpoint pro-tein PD-L1 is overexpressed on tumor or immune cells (12)(13)(14)(15)(16) show even greater clinical benefit from these therapies.…”
Section: Introductionmentioning
confidence: 99%